Teaching dynamics to enhance critical thinking and knowledge socialization in the mathematics classroom - Dominguez, Angeles (Frontiers in Education, 2024)
Building the future of education together means that, as educators, we need to promote innovation and educational strategies in our classroom to foster the development of skills such as critical thinking and argumentation. Moreover, we should encourage using technology as an efficient and effective tool to solve complex problems. Mathematics is a cornerstone in the education of engineering students. However, students' mathematic classroom experiences have only presented them with a rigid and pure side to the discipline. Active learning strategies foster the development of competencies such as critical thinking and argumentation while generating knowledge socialization and learning democratization. The active learning dynamics were conducted in first-year undergraduate calculus course for engineering and are based on collaborative learning, modeleliciting activities, and the use of technology. Students reported that being actively involved and interacting with classmates and tools made them enjoy the class, broaden their view of mathematics, and connect with contexts from other disciplines. Moreover, these dynamics favor different types of formative assessment for students, self-and peer-assessment, and for teachers about the students learning and the design of the activity. Based on educational research, the design of the dynamics is innovative in the combination of implementations used to potentiate the benefits of a studentcentered learning environment and the socialization of knowledge.